Utilização da nota fiscal eletrônica no controle da arrecadação tributária sob a ótica dos gestores fazendários: estudo na Secretaria da Fazenda do Estado do Ceará - Pessoa, Everton Bessa (2012)
The Electronic Invoice becomes increasingly a reality. Since late 2011, virtually all interstate operations are being covered up with the electronic document. This tool is born with a view to minimize frauds in fiscal operations, bringing the possibility of creating real-time controls, resulting several beneficial effects on tax administration. This study aimed to address this issue, having as main purpose to analyze the use of Electronic Invoice control of tax collection from the perspective of managers of the Department of Finance of the State of Ceará. To achieve this goal, this research searched first to verify the managers level of reliability related to the data extracted from the Electronic Invoice. And then, tried to identify as many controls that are currently being used and to investigate those that are being developed at the State of Ceará Secretary of Treasury based on this tool. Finally, this study sought to observe the effects of using these controls in the view of tax managers. As a theoretical support the study used a literature review, focusing on tax administration and electronic invoices. A case study about State of Ceará Secretary of Treasury was the methodology adopted with collected information regarding the perception of tax managers through questionnaires and interviews, analyzed using ATLAS.ti version 6.2 and Likert scale. The results obtained in the research concluded that tax managers, responsible for controlling the state revenues from taxes, have a good level of confidence regarding the use of data extracted from Electronic Invoice. As well, various controls, based on this information, have been optimized, implemented or are under implementation, and, in general, the use of these controls bring positive effects to the monitoring of tax collection of Ceará State.